The Effectiveness of Zakat Services in Increasing Economic Independence - Taufiq Akbar; Amri Amri; Satrama Royal Harinata; Muhammad Ali (Publikasi Indonesia, 2024)
The effectiveness of zakat services is an achievement of every series of service activities provided by the National Amil Zakat Agency in providing integrated zakat management actions in several service programs, one of which is in increasing economic independence in the community, especially in people who receive/use this zakat service, which in general is still far from being economically independent, so that the achievement of the program, of course, will increase economic independence and have an impact on the welfare of the community itself. In this study, an explanatory research method was used with a quantitative approach and 103 respondents were taken. The data processing and distribution in this study were analyzed using path analysis with the AMOS/Structural Equation Model (SEM) V.22 program.The results showed that the effectiveness of zakat services could increase the level of economic independence positively and significantly in children (cr=4.561:p = 0.048).